Discussion on ecological restoration strategy of water conservancy project -- A case study of Shirase Reservoir in Quanzhou City - Fan Shizhe; Li Mingge; Huang Jingwen; Cheng Yuqing; Zhou Wenye (E3S Web of Conferences, 2024)
Because of the water conservancy project construction to the environment has brought a lot of damage, the state for environmental pollution and damage problems began to carry out a comprehensive restoration, for the relevant environmental protection and restoration policies are also improving, with the implementation of relevant measures, ecological water conservancy projects will play a vital role in environmental governance. In order to put forward suggestions for ecological restoration of white rose reservoir, this paper puts forward suggestions for ecological restoration from the geographical location of the water conservancy project, the measures in the construction process and the operational measures after completion, so as to restore the ecological role played by the ecological area before the completion of the water conservancy project and reduce the secondary pollution and damage to the environment in the operation process after it. This paper discusses the importance of ecological water conservancy project in environmental governance, and takes Shirase reservoir as an example, puts forward the ecological restoration suggestions for the water conservancy project. In order to restore the ecological function of the area before the water conservancy project and reduce the secondary pollution and damage in the operation process, it is suggested to improve the area from three aspects: geographical location, construction process and operation measures after completion. Through the implementation of ecological restoration measures, it will help to realize the harmonious symbiosis between man and nature.